2021
DOI: 10.1109/access.2021.3052060
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Diffusion Mechanisms of Methanol in Paper/Oil Insulation Based on Molecular Dynamics Simulation

Abstract: Methanol is regarded as an available indicator to analyze the aging condition of cellulose insulation. However, the diffusion mechanism of methanol molecules in the paper-oil insulation system is still unclear, since it cannot be explored by using only experiments. Given this issue, the molecular dynamics simulations were performed to investigate the diffusion mechanism of methanol molecules. In the current work, the mean square displacement of methanol during the diffusion process was calculated and analyzed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Wherever, cellulosic insulating material is impregnated with the MO, which enhances the insulation integrity as well as the life cycle of insulation medium. Solid insulating material is made upon the cellulosic insulating materials [3]. The kraft paper is used to provide insulation between the turn of transformer windings.…”
Section: Introductionmentioning
confidence: 99%
“…Wherever, cellulosic insulating material is impregnated with the MO, which enhances the insulation integrity as well as the life cycle of insulation medium. Solid insulating material is made upon the cellulosic insulating materials [3]. The kraft paper is used to provide insulation between the turn of transformer windings.…”
Section: Introductionmentioning
confidence: 99%
“…In previous simulations of the diffusion behaviour of water molecules or gas molecules in mineral and vegetable oils, it has been demonstrated that the diffusion coefficients of those impurity molecules are generally higher in mineral oils than in vegetable oils, and their diffusion abilities are closely related to the molecular mass and polarity [25][26][27]. While in the insulating paper, the diffusion coefficients of impurity molecules are drastically reduced compared to those in transformer oil [28][29][30]. Moreover, according to the MD simulations conducted by Tang et al, the addition of nanoparticles, whether in cellulose paper or transformer oil, could significantly reduce the diffusion coefficients of impurity molecules in oil-paper insulation as the nanoparticle surface exhibits a strong attractive potential that limits the migration of impurity molecules [31][32][33].…”
mentioning
confidence: 99%